2022
DOI: 10.1002/celc.202200385
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cycling Performance of Fe‐doped LiMn2O4 Truncated Octahedral Cathodes for Li‐Ion Batteries

Abstract: LiMn 2 O 4 (LMO) with a spinel crystal structure is a promising cathode for next-generation Li-ion batteries (LIBs), owing to its low cost and high operating voltage of ~4.4 V. However, due to the Jahn-Teller distortion effect, LMO typically exhibits deteriorated cycling performance, owing to the dissolution of Mn into a liquid electrolyte. In this study, Fe-doped truncated octahedral LMO cathodes with different concentrations were synthesized to improve LMO stability in LIBs. The Fe-doped truncated octahedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Combining the calculated lattice parameters of the samples (shown in Table 1), the growth pattern of LMO in a high temperature environment is closely related to the concentration of VOs in the lattice, which may lead to increased lattice distortion in severe cases. [35][36][37] The deoxygenated sample recovered the particle morphology after the oxygenation treatment, but the LMO-4 sample had blunt particle edges due to the irreversible loss of lithium by hightemperature annealing. The lattice structure shrinks due to changes in the composition of the material phase and the degree of defects after oxidation treatment, so that the particle morphology and size change significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Combining the calculated lattice parameters of the samples (shown in Table 1), the growth pattern of LMO in a high temperature environment is closely related to the concentration of VOs in the lattice, which may lead to increased lattice distortion in severe cases. [35][36][37] The deoxygenated sample recovered the particle morphology after the oxygenation treatment, but the LMO-4 sample had blunt particle edges due to the irreversible loss of lithium by hightemperature annealing. The lattice structure shrinks due to changes in the composition of the material phase and the degree of defects after oxidation treatment, so that the particle morphology and size change significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of the surface orientation of the LMNFA cathode materials is determined by calculating the intensity ratio of the planes (111) and (400) (Table ). From the table, it can be observed that the intensity ratio value of the (111)/(400) plane for LMNFA2 material is slightly more than that of LMNFA1 and LMNFA3, which is due to the dominance of the (111) plane in the crystal structure . In addition, it also shows the dominant facets of the (111) plane, which corresponds to the truncated type .…”
Section: Resultsmentioning
confidence: 95%
“…From the table, it can be observed that the intensity ratio value of the (111)/(400) plane for LMNFA2 material is slightly more than that of LMNFA1 and LMNFA3, which is due to the dominance of the (111) plane in the crystal structure. 24 In addition, it also shows the dominant facets of the (111) plane, which corresponds to the truncated type. 9 The Mn 3+ (0.64 Å) ions in LiMn 2 O 4 are substituted by Fe 3+ (0.65 Å) ions, which results in a low-angle shift according to Bragg's law.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Several groups have worked on stabilizing this disproportionation redox issue by employing Ni in the structure alongside the minimal doping of other elements. 5,[75][76][77][78] The final material with the formula of Li x-Ni 0.5 Mn 1.5 O 4 (LNMO) improves the operating voltage up to B4.8 V, where some works reported up to B5 V in half-cell testing scenarios. 44,73,79 Single-crystal LNMO spinel materials by Liu et al have shown superior cycling performance, retaining up to B99% of capacity cycling at higher rates for 2000 cycles.…”
Section: Types Of Cathode Materialsmentioning
confidence: 99%